The impact of the global economic crisis on the finances of non-governmental sport organizations in Slovenia remains to be seen - Gregor Jurak; Wladimir Andreff; Stevo Popović; Damjan Jakšić; Jakob Bednarik (Universidade Estadual Paulista (UNESP), 2014)
This paper examines the impact of the global economic crisis on revenues on all non-governmental sport organizations (sport NGOs) in Slovenia, as a small European economy. Five types of operating revenues of all sport NGOs from 2007 to 2010 have been analyzed. We found that the overall trend of sport NGOs revenues does not correspond exactly to the trends of the Slovenian economy. The greatest financial impacts were experienced in grassroots sport, while professional sport NGOs have increased their operating revenues, mostly due to increases of public revenues. The findings suggest that the true impact of the recession on Slovenian sport NGOs remains to be seen. We conclude that the ongoing recession will affect grassroots sport the least, while semi-professional and professional sport NGOs will be under financial threat. Because of the synergistic effects of different types of NGOs, this could affect the sustainability of Slovenian sport.